Antifungal effects of Lactobacillus acidophilus and Lactobacillus plantarum against different oral Candida species isolated from HIV/ AIDS patients: an in vitro study. Issue 1 (1st January 2020) - Salari, Samira; Ghasemi Nejad Almani, Pooya
ABSTRACT: Oropharyngeal Candidiasis (OPC) is an opportunistic fungal infection occurring in immunocompromised patients such as HIV/AIDS. The purpose of this study was to evaluate the antifungal properties of Lactobacillus acidophilus and Lactobacillus plantarum on different Candida species isolated from oral cavity of HIV/AIDS patients compared to Fluconazole (FLC). In this study, the antifungal effects of both cells and cell-free supernatants (CFSs) of L. acidophilus and L. plantarum were investigated against different oral Candida species by co-aggregation, agar overlay interference and broth microdilution assays, respectively. Our results showed that the highest co-aggregation ratio of the two tested Lactic acid bacteria (LAB) was observed for C. krusei . Both L. acidophilus and L. plantarum at cell concentrations 10 10 to 10 2 cfu/ml were able to inhibit the growth of most of the oral Candida species, except for C. albicans, and to some C. krusei . In this study, MIC and MFC values for CFS of L. acidophilus ranged from 100 to 200 µl/ml and 100 to 200 µl/ml, respectively, and MIC and MFC values for CFS of L. plantarum were 50 to 200 µl/ml and 50 to 200 µl/ml, respectively. The ranges of MIC and MFC for FLC were 256–1024 µg/ml and 512–2048 µg/ml, respectively. C. albicans and C. parapsilosis displayed the highest and least susceptibility to CFSs of two LAB, respectively. Our findings showed that both cells and CFSs of L. acidophilus and L. plantarum had antifungal effects against oral Candida species.